Potentiation of cancer immunogenicity by targeting PARP - Victoria Klepsch; Gottfried Baier; Dominik Humer (Journal for ImmunoTherapy of Cancer, 2025)
A team of scientists led by Quigley Goa demonstrates that Poly(ADP-ribose) polymerase (PARP) inhibitors (PARPi) can induce tumor cell death in a manner that allows immune cells to better recognize and attack the tumor. Specifically, PARPi are approved for the treatment of tumors with homologous recombination repair defects. Due to their pre-existing DNA repair defects, PAPRi appear to be a pharmacological tool to induce immunogenic cell death (ICD). Remarkably, therefore, both increased tumor neoantigen generation and reprogramming of the tumor immune microenvironment to an immunostimulatory state antagonize impending immunosuppression and consequently promote enhanced antitumor immunity. This finding strongly supports PARPi targeting as a promising approach to alleviate intratumoral effector T cell immune dysfunction, particularly in the context of immunotherapy resistance. In conclusion, this well-defined relationship between PARPi-based chemotherapy and ICD of tumor cells may offer substantial potential as a valuable sensitizer for future combinatorial cancer immunotherapy, which together with immune checkpoint therapy, but potentially also with others including cancer vaccines, is likely to be more effective against defined solid tumors and better promote host-protective cancer immune control (see related article by Xia et al, 2024).